2021
DOI: 10.1093/ofid/ofab160
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Dissemination and Axillary Web Syndrome in Primary Cutaneous Tuberculosis Secondary to Needlestick Injury

Abstract: Cutaneous tuberculosis secondary to skin inoculation of Mycobacterium tuberculosis is uncommon but it can occur in the healthcare settings. Herein, we report an unusual case of primary cutaneous tuberculosis of the thumb following a needlestick injury. The infection progressed with a necrotic granuloma, lymphatic dysfunction as visualized by near-infrared fluorescence lymphatic imaging, and the development of an axillary web syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It has been reported that lymphadenopathy in the axillary region occurs as a side effect of collagenase injections into the palms [28], and the involvement of the lymphatic system affected by collagenase injections has been described. Finally, one case of AWS has been reported due to lymphatic vascular damage associated with axillary lymph node dissemination of tuberculosis [23]. In this report, drug-induced tuberculosis was treated.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It has been reported that lymphadenopathy in the axillary region occurs as a side effect of collagenase injections into the palms [28], and the involvement of the lymphatic system affected by collagenase injections has been described. Finally, one case of AWS has been reported due to lymphatic vascular damage associated with axillary lymph node dissemination of tuberculosis [23]. In this report, drug-induced tuberculosis was treated.…”
Section: Discussionmentioning
confidence: 86%
“…Herein, we report a rare case of AWS after venous blood sampling in a patient without a history of axillary surgery. To the best of our knowledge, reports of AWS without direct invasion, such as postoperative breast cancer surgery, sentinel node dissection, or sentinel node biopsy, are rare, with only twelve cases reported in PubMed [16][17][18][19][20][21][22][23][24][25][26][27]. The cases were summarized on 20 May 2023 by searching the keywords 'Axillary Web Syndrome' in PubMed.…”
Section: Introductionmentioning
confidence: 99%
“…FIGURE 10 (A) Normal lymphatic drainage in the unaffected right arm and dermal backflow in the left arm of a subject with unresolved cutaneous Mycobacterium tuberculosis. Reproduced with permission from(Malek et al, 2021). (B) Dermal backflow in the foot of a patient with HIV with no other conditions that could be associated with lymphatic dysfunction.…”
mentioning
confidence: 99%